RVA Works : empowering entrepreneurs for big change - Mulloth, Bala; Fickett, Dale (London : SAGE Publications: SAGE Business Cases Originals, 2021)
RVA Works (a shortening of Richmond, Virginia Works) is a public charity, which has demonstrated superior efficacy in educational programming for entrepreneurship. Since 2014, their work has primarily focused on providing pathways to business ownership for ethnic minorities, women, and lower-income people. Through a network of sponsors and volunteers, they have provided a weekly entrepreneur presentation series, mentorship, a cohort-based training curriculum, pro bono professional services, and other referrals. This work has raised entrepreneurs' household income levels, created new jobs, and provided strong community role models. This case allows students to evaluate challenges faced by micro-enterprise owners across America and understand the frameworks for boosting community entrepreneurship. Students will also be able to assess RVA Works' strategic growth goals, particularly considering the adoption of technology into the organization's business model. The case ultimately gives students tools to help them decide on what action RVA Works can take to maximize the extent of their social impact in balance, within the financial constraints of an operating charity.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Virginia -- Richmond -- Case studies